Analisis Model Discovery Learning Sebagai Upaya Meningkatkan Pemahaman Konsep Tata Ruang Kantor - Maslukah Maslukah; Brillian Rosy (Universitas Negeri Surabaya, 2020)
This article is aimed to analyze how the discovery learning model can improve students understanding of office layout concepts. Basic competence regarding office layout is aimed for students to identify and formulate office layout problems through collecting the data, processing the data, and communicating the concepts of office layout. In the implementation of office layout learning, material delivered thorugh a direct learning model with lecture method is difficult to understand and less stimulating the students activity and ability. The direct learning model with lecture method is not appropriate with the provision of the current curriculum, 2013 curriculum in 2017 revision which focuses on student centered learning. œBased on the current curriculum provision, learning model that focuses on the students themselves in the learning process is necessary to apply in order to stimulate the students activeness, abilities, and interests in improving the understanding of concept in the teaching and learning process. The discovery learning model is the proper model to improve understanding of office layout concept, œbecause the model aims to stimulate the students to be more active in learning activities to develop creativity and ability to think rationally and critically in problem solving. The basic competency regarding office layout will be useful not only in the workplace but also useful for daily life. The type of this research is conceptual which proves that the discovery learning model is the right choice as an effort to improve the concept of office layout.